Legal Analysis And Education On Blessing In The School Environment - Emiel Salim Siregar; Dicky Apdilah (LEGAL BRIEF, 2022)
The school environment is a meeting place between teachers and students, with a philosophy to improve students' intellectuals and produce an education that has high dedication and morals and respects others. In this study, analysis and education were conducted on the law of bullying among students and children. This research method aims to analyze the law that regulates bullying. The method used is by tracing the law that applies to the perpetrators of bullying and the psychological impact on the victim